Inequality in child immunization coverage in Ethiopia: evidence from Expanded Program for Immunization coverage survey - Yada, Dereje Y.; Getachew, Theodros; Getnet, Misrak; Taye, Girum; Taddele, Tefera; Defar, Atkure; Tadele, Ashenif; Zeru, Arega; Getachew, Fikresilassie (Eximia, 2023)
Background: Immunization is one of the cost-effective public health interventions, and can be used to prevent life-threatening childhood illnesses. This study aimed to assess disparities in child immunization coverage in Ethiopia. Method: Data from the 2012 Ethiopian Expanded Program for Immunization coverage survey was used. In this study, absolute and relative equity analysis was employed based on socioeconomic variables Result: Equity analysis was conducted in 3,748 subjects out of 3,762 child caregivers’ data. The concentration index among the poorest and richest group for BCG immunization coverage was 11%, OPV 3 was 13.3%, Pneumococcal 3 was 38.6%, Pentavalent 3 was 21.5%, Measles was 12.9%, Vitamin A supplementation was 8.9%, and full immunization was 38.6%. Conclusion: Inequalities were observed in child immunization coverage across the socioeconomic groups, with the better-off wealth status, urban residents, and children from an educated mother being more likely to be vaccinated.